GURU PENDIDIKAN AGAMA KRISTEN SEBAGAI MENTORING BAGI KORBAN BULLYING - Tryastuti Wuryandari; Bertha Apricia; Syanti Dewi (Bethel Press, 2021)
This study aims to explore the role of Christian Religious Education (CRE) teachers as mentors for bullying victims in schools through a qualitative approach using library research. The literature review reveals that bullying is a social and educational issue with significant impacts on the psychosocial development of victims. CRE teachers play a strategic role as mentors who integrate Christian values such as love, forgiveness, and self-identity affirmation to support victims’ recovery. The proposed mentoring model combines pedagogical, psychological, and spiritual approaches while involving support from the school and faith communities. The findings emphasize the importance of CRE teachers as mentors in fostering inclusive school environments and building resilience among bullying victims.